Investigation and management of stridor in neonates. Issue 4 (April 2023) - Shanthakunalan, Karthika; Wijayasingam, Giri; Sudarshan, Purushothaman; Prayle, Andrew; Daniel, Mat
Abstract: Stridor is an uncommon yet potentially serious symptom in neonates. It is indicative of airway obstruction. This short article describes how to approach a baby with stridor. Assessment and investigation should proceed in a structured manner. Important clues about the likely cause can be determined using a combination of a careful history and clinical examination. The character and nature of any stridor, combined with information about the onset of symptoms are particularly important. These may help to determine the best initial investigations, including direct visualization of the airway and management. There are different types of airway endoscopy, ranging from awake flexible laryngoscopy that examines to the level of the vocal cords, to rigid laryngotracheobronchoscopy under general anaesthesia that allows additional examination of the subglottis, trachea and main bronchi, and to flexible bronchoscopy that assesses the respiratory tract further still and is particularly useful in assessment of tracheomalacia. A cross-speciality approach is often required to secure the best outcomes. This article is aimed at the whole team who will be involved in dealing with babies with stridor, including anaesthetists, paediatricians, advanced care practitioners and ENT doctors.